Peran Leverage dan Pengungkapan Modal Intelektual terhadap Risiko Perusahaan (Studi pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia, 2017-2021) - Asih Marini Wulandari (Universitas Halu Oleo, 2023)
This study aims to examine the effect of leverage and disclosure of intellectual capital, on company risk. Conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021 with a population of 142 companies. The sample was selected using purposive sampling with a total sample of 21 companies. The analysis was carried out using SEM analysis with the WarpPLS approach. The results of the study show that leverage has a significant effect on disclosure of intellectual capital and company risk. Disclosure of intellectual capital is also proven to have a significant influence on corporate risk. It can be said that the results of this study are useful for potential investors to estimate company risk in making investment decisions. Research results are also important for company management to manage company risk.Â Key words: leverage, intellectual capital disclosure, firm riskÂ